LOTE learning motivation in multilingual workplace - Cheng 程倩, Qian; Wang, Yawen; Zhao 赵珂, Ke (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This study aims to investigate the LOTE learning motivation profiles of adult learners at a multilingual workplace and the interplay of multilevel factors affecting LOTE learning motivation. To address the research objectives, we undertook this case study on a Spanish bank subsidiary in China by conducting semi-structured interviews with three senior managers at varying LOTE language proficiency levels. Premised on a person-in-context relational perspective, interview data analysis revealed the participants LOTE motivation change trajectories resulting from the dynamic interplay of related factors. Further analysis of the narratives identified the interplay between key contextual and individual factors affecting the participants’ LOTE learning motivation at different levels, namely social cultural and institutional. The results emphasise the person-in-institutional context relation and the significance of team climate, language beliefs and identity in influencing LOTE learning motivation
Keywords: LOTE learning motivation; multilingual workplace; multinational corporations